Public workers : government employee unions, the law, and the state, 1900-1962 - Slater, Joseph E., 1960- (ILR, 2004)
"Public Workers is the first book to analyze why public sector labor law evolved as it did, separate from and much more restrictive than private sector labor law, and what effect this law had on public sector unions, organized labor as a whole, and by extension all of American politics. Joseph E. Slater shows how public sector unions survived, represented their members, and set the stage for the most remarkable growth of worker organization in American history."--BOOK JACKET.